PENGARUH AIRLINES TANGIBLES, TERMINAL TANGIBLES, PERSONNEL QUALITY, EMPATHY DAN AIRLINE IMAGE TERHADAP CUSTOMER SATISFACTION: (Studi Pada Penumpang Garuda Indonesia) - Sagala, Roslinda; Sinaga, Ria Veronica (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this study was to analyze the influence of Airlines Tangibles, Terminal Tangibles, Personnel Quality, Empathy, and Airline Image partially and simultaneously on Customer Satisfaction of Garuda Indonesia Aircraft users. The number of samples was 96 respondents with primary and secondary data collection techniques, linear regression analysis techniques. double. The results showed that respondents' responses to the Airlines Tangibles variable were more dominant in stating that Airlines Tangibles (Relating to the interior of the aircraft used by airlines) owned by Garuda aircraft was very good, more dominantly stating that Terminal Tangibles (Relating to facilities and infrastructure at the airport) which owned by the airport is good, the Personnel Quality variable is more dominant stating that Personnel Quality (relating to the quality of flight attendant service on the plane) is good, the Empathy variable is more dominant stating that Empathy (relating to sincere and individual attention from flight attendants to passengers) is good, Airline Image variable is more dominant stating that Airline Image (relating to customer or consumer perceptions of the brand or company service as a whole) is good, the Customer Satisfaction variable is more dominant stating that Cu Customer Satisfaction (Related to a person's feelings after he compares (evaluates) between expectations and the results (performance) he feels after he buys or uses a product or service) is satisfactory. The Garuda Indonesia airline needs to know consumer expectations regarding airline tangibles in order to increase customer satisfaction. It is also necessary to pay attention to the condition of the facilities and infrastructure available from the airport side. This is related to the availability of executive lounges at the airport which can provide comfort to passengers while waiting for departure. To increase customer satisfaction, Garuda Indonesia needs to know what expectations consumers have regarding terminal tangibles so as to increase customer satisfaction. To increase customer satisfaction, Garuda Indonesia needs to know what expectations consumers have regarding personnel quality, Empathy and Airline Image so as to increase customer satisfaction.